2017
DOI: 10.1002/pd.5055
|View full text |Cite
|
Sign up to set email alerts
|

Experience of carrier couples identified through a population‐based carrier screening pilot program for four founder autosomal recessive diseases in Saguenay–Lac‐Saint‐Jean

Abstract: Our results emphasize the informational needs of couples to make informed decisions and the importance of post-test counseling for those with positive results. Our findings can inform counseling procedures in expanded carrier screening. © 2017 John Wiley & Sons, Ltd.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 17 publications
0
15
0
Order By: Relevance
“…Should a couple then elect invasive diagnostic testing for their pregnancy, final results often take two to three weeks to become available. Patients have previously reported experiencing significant anxiety after receiving positive carrier screening results, regardless of whether or not the information will be used for preparation or for consideration of termination . The time spent waiting for partner results compounded by the gestational age constraints for pregnancy termination can heighten this anxiety for some patients who may consider termination if a genetic diagnosis is confirmed.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Should a couple then elect invasive diagnostic testing for their pregnancy, final results often take two to three weeks to become available. Patients have previously reported experiencing significant anxiety after receiving positive carrier screening results, regardless of whether or not the information will be used for preparation or for consideration of termination . The time spent waiting for partner results compounded by the gestational age constraints for pregnancy termination can heighten this anxiety for some patients who may consider termination if a genetic diagnosis is confirmed.…”
Section: Discussionmentioning
confidence: 99%
“…Patients have previously reported experiencing significant anxiety after receiving positive carrier screening results, regardless of whether or not the information will be used for preparation or for consideration of termination. 4,7,9 The time spent waiting for partner results compounded by the gestational age constraints for pregnancy termination can heighten this anxiety for some patients who may consider termination if a genetic diagnosis is confirmed. This may be particularly salient in states where the limit for termination has been shortened.…”
Section: Gjb2-related Nonsyndromic Hearing Loss and Deafnessmentioning
confidence: 99%
See 2 more Smart Citations
“…A recent population-based study describing couples' experience with carrier screening revealed that prospective carrier parents are not aware of screening programs, though, upon taking the test, they appreciated knowing their risk thereby recognizing the test's importance [32]. There are many benefits in combining an extended carrier screening test with a NIPT.…”
Section: Discussionmentioning
confidence: 99%